(iii) 13 (z - 4) - 3 (z - 9) - 5 (z + 4) = 0
Answers
Answered by
9
Answer:
(✪HAY MATE✪)
YOUR ❝Qᴜᴇsᴛɪᴏɴ❞
(iii) 13 (z - 4) - 3 (z - 9) - 5 (z + 4) = 0
Step-by-step explanation:
ANSWER IS GIVEN WITH ATTACHMENT
❥ I HOPE IT WILL HELP YOU
Attachments:
![](https://hi-static.z-dn.net/files/d8d/35c8e78501951d122ba8cf380f7bdd0f.jpg)
Answered by
1
Answer:
→ 13z-52-3z+27-5z-20 =0
→5z - 45 =0
→5z = 45
→z = 45/5
→z = 9
Similar questions
English,
3 months ago
Social Sciences,
3 months ago
Math,
6 months ago
Math,
6 months ago
History,
1 year ago
Social Sciences,
1 year ago
Math,
1 year ago